Pengaruh Resiliensi Karyawan terhadap Kinerja Karyawan melalui Kepuasan Hidup - Ocktafian, Qikki (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The focus in this study is to discuss the effect of employee resilience on employee performance with life satisfaction as a mediation variable. The object of this research is the nurses at Rumah Sakit Islam Surabaya with the respondents is 71 nurses. This study used quantitative methods to process questionnaires that have previously been distributed online. Then used statistical analysis Partial Least Square with smartPLS 3.3 program. This study shows that there is a positive and significant influence between employee resilience to performance and employee life satisfaction. However, there was no significant influence found between satisfaction on employee performance. Furthermore, the relationship between employee resilience and employee performance through life satisfaction variables as a mediation was not found to have a significant effect. The implication of this research is that to maintain and improve the performance of nurses, it is necessary to have adaptive and resilient nurses in facing various challenges in the world of work, regardless of the level of life satisfaction of nurses.